Screening needs and expectations of patients with vascular access due to chronic hemodialysis (Journal of Health Sciences, 2016)
There is a lack of data about daily difficulties and life quality, especially among young patients having arteriovenous fistula (AVF) affected by (pseudo)aneurysm. In this retrospective cohort study, 195 patients with AVF were followed up from May to June 2015. An unstandardized questionnaire was used for the evaluation of patients’ screening needs and expectations. Retired married men in their sixties, with completed secondary education, represented the majority of patients with AVF in this study. The patients had a positive attitude towards the disease and AVF, and they received the majority of information related to the care and treatment of AVF from the medical personnel and doctors in selected dialysis centers. Employed, well-educated single men, aged between 21 and 40 years, had the highest interest in having an aesthetic correction of AVF, especially due to the formation of (pseudo)aneurysm at the AVF site. Establishment of rules for reconstructive procedures of AVF, once circulatory and hemodynamic stability is achieved after renal transplantation, is suggested in addition to establishing criteria for determining vascular access affected by (pseudo)aneurysm.